Dharma Kasogatan & Padma Buwana Communities: Collaborative Rituals and Social Challenges at Mangir Lor Hamlet, Yogyakarta - Nusya Kuswantin (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
This paper discusses the social challenges faced by Utiek Suprapti during her efforts to revive rituals in order to pray for ancestors under a newly-constructed lingga-yoni temple at her own house yard at Mangir Sub-village, Bantul Regency, Yogyakarta Province. She faced objection by local people supported by police chief when she was conducting collaborative ritual with Buddhist Dharma Kasogatan community in November 2019. As if local people were ignorant what kind of ritual she performed, eventhough the previous year of 2018 the similar ritual with the same intention had successfully been conducted. After the objection became viral news in the social media, in front of local apparatus at the Office of Bupati Bantul, Utiek Suprapti declared herself as adopting Hindu as her religion. In order to find solution towards the objection, Utiek Suprapti has been advocated by Gemayomi (Yogyakarta Popular Movement against Intolerance) including in mediating with local residents and apparatus. By applying participant observation and interview as data collecting methods, this article tries to answer how the two communities of different religious teachings are able to conduct collaborative rituals harmoniously and why local residents expressed their objection against the collaborative ritual.